2008
DOI: 10.1089/gte.2008.0042
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of Sporadic Parkinsonism and Late-Onset Alzheimer's Disease in a Brazilian Male with theLRRK2p.G2019S Mutation

Abstract: Mutations in the leucine-rich repeat kinase 2 (LRRK2) gene represent the most common known genetic cause of inherited and idiopathic Parkinson's disease (PD) in different populations. The predicted multifunctionality of LRRK2 product and the pleomorphic pathology associated with LRRK2 mutations place this gene as a potential candidate for other neurodegenerative disorders, mainly Alzheimer's disease (AD). We report a Brazilian male expressing both late-onset AD and slowly progressive parkinsonism signs, and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…DISCUSSION Our findings are in agreement with the majority of reports of the clinical features of LRRK2-associated PD, which indicate that the phenotype is not distinguishable from iPD. There have been individual exceptions to this, however; atypical cases with supranuclear gaze palsies, 8 prominent dementia, 9 or psychosis unrelated to medications. 10 Tremor was a more common presenting feature in our LRRK2 group compared with iPD, and this was also found in a large international study.…”
Section: Figurementioning
confidence: 99%
“…DISCUSSION Our findings are in agreement with the majority of reports of the clinical features of LRRK2-associated PD, which indicate that the phenotype is not distinguishable from iPD. There have been individual exceptions to this, however; atypical cases with supranuclear gaze palsies, 8 prominent dementia, 9 or psychosis unrelated to medications. 10 Tremor was a more common presenting feature in our LRRK2 group compared with iPD, and this was also found in a large international study.…”
Section: Figurementioning
confidence: 99%
“…The incidence of tremor, however, seems to be elevated in LRRK2 carriers indicating that LRRK2 mutations most likely lead to tremor-dominant disease [Haugarvoll et al, 2008;Nuytemans et al, 2008;Paisan-Ruiz et al, 2004]. On the other hand, isolated studies have also reported LRRK2 mutations in carriers with a clinical diagnosis of sporadic PD with late-onset AD as well as CBD, PSP, or frontotemporal dementia (FTD) [Chen-Plotkin et al, 2008;Santos-Reboucas et al, 2008;Spanaki et al, 2006].…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, most genetic screens have been limited to PD clinic populations, with only a few studies referring to other neurodegenerative diseases. LRRK2 mutation has been assumed to play an upstream influence on the etiology of not just PD but also several α-synuclein and tau pathologies, including Alzheimer disease (AD) [ 37 ]. A research reported two LRRK2 mutation carriers who showed cognitive impairment, leading to clinical diagnoses of corticobasal syndrome (CBS) and primary progressive aphasia (PPA), a subtype of frontotemporal dementia (FTD).…”
Section: Clinical Features Of Lrrk2-associated Parkinsonismmentioning
confidence: 99%